Bibliometric analysis of digital-based education services - Nuril Furkan; Sumarno Sumarno; Ahmad Budidarma (Jurnal Office, 2022)
Finding the ideal solution is now largely hampered by the availability of digital-based education providers. This article uses the Vosviewer program is used to carry out the bibliometric process. Numerous papers from throughout the globe have made significant contributions to the discussion of this phenomenon. In the period of the COVID-19 pandemic, developed nations have done study on digitally based education services by offering findings that are able to accomplish maximum job productivity. The information was gathered from a variety of pertinent international journal references from several sources, including dimension.ai, publish, or peris, which served as the standard for locating pertinent references.